Comprehensive analysis of polymorphisms in the HLA-G 5' upstream regulatory and 3' untranslated regions in Brazilian patients with systemic lupus erythematosus. - Catamo, E; Addobbati, C; Segat, L; Sotero Fragoso, T; Tavares Dantas, A; de Ataíde Mariz, H; Ferreira da Rocha Junior, L; Branco PintoDuarte, A L; Coelho, A V C; de Moura, R R; Polesello, V; Crovella, S; et al. (Tissue Antigens, 2015)
This study aims to comprehensively analyze human leucocyte antigen (HLA)-G polymorphisms association with susceptibility to systemic lupus erythematosus (SLE) development and clinical manifestations. The HLA-G 5' upstream regulatory region (URR), 3' untranslated region (UTR) and a cytosine deletion at exon 3 (ΔC, HLA-G*0105N allele) were analyzed in 114 SLE patients and 128 healthy controls from North East Brazil. The +3003T>C (rs1707) C allele and the HG010101c extended HLA-G allele were significantly more frequent in SLE patients than healthy controls (+3003C allele frequency: 12% in SLE patients vs 6% in controls; odds ratio (OR), 2.10, 95% confidence interval (CI), 1.06-4.28, P = 0.026; HG010101c frequency: 11.8% in SLE patients and 6.3% in controls; OR, 2.14, 95% CI, 1.01-4.51, P = 0.046) and were associated with susceptibility for disease development. Other polymorphisms were associated with different clinical manifestations. Although HLA-G role in SLE disease is far from being elucidated yet, our association study results along with a systematic review and meta-analysis suggest that HLA-G might be able to slightly modulate the complex SLE phenotype (pooled OR, 1.14, 95% CI, 1.02-1.27, P = 0.021).